Use of tacrolimus to prevent acute kidney graft rejection in sensitized patients - O. N. Rzhevskaya; A. V. Pinchuk; R. V. Storozhev; I. V. Dmitriev (Трансплантология (Москва))
The emergence of new immunosuppressants, such as the macrolide drug tacrolimus (prograf), has recently become one of the most important advances in transplantology. Tacrolimus belongs to calcineurin inhibitors and differs from cyclosporine in a rapider and uniform bile acid-independent absorption, causing a reduction in the individual variability of the blood concentration of the active ingredient. On renal transplantation in sensitized patients and/or repeated allografting, the use of tacrolimus makes it possible to reduce the percentage of hormone-resistant crises by more than twice and to prevent intractable acute rejection crisis.